264. A 20-year Study of Intracranial Pyogenic Complications of Sinusitis in Children. (4th December 2021) - Tat, Jennifer; Smiljkovic, Mina; Richardson, Susan E; Campigotto, Aaron; Cushing, Sharon; Wolter, Nikolaus E; Dirks, Peter; Bitnun, Ari
Abstract: Background: Intracranial pyogenic complications of sinusitis in children are relatively uncommon but can lead to serious sequelae. The objective of this study was to characterize the clinical, epidemiologic and microbiologic characteristics of children with such complications over a 20-year period (2000- 2019). Methods: Single-center retrospective chart review. Cases were identified based on International Classification of Diseases (ICD)-10 diagnostic codes (intracranial abscess or granuloma, extradural and subdural abscess, Pott's puffy tumor, acute or chronic sinusitis) and by reviewing all microbiological samples of intracranial pus, tissue or fluid. Results: 108 cases of clinically and/or radiologically diagnosed sinusitis were included after review of 1591 charts. The majority were adolescents (median age 12, IQR 9-14); 72 were male (67%). The most common presenting symptoms were fever (84%), headache (87%) and symptoms of upper respiratory tract infection (57%). Median symptom duration was 10 days (IQR 5-21) and 55 cases (51%) received oral antibiotics prior to admission. The most frequent complications were epidural empyema (n=50, 46%), subdural empyema (n=46, 43%) and Pott's puffy tumor (n= 31, 29%). 50% (n=54) underwent neurosurgery, of which 20% (n=11) required multiple craniectomies. 38% (n=41) underwent otolaryngological surgery. Microbiological data from sterile specimens demonstrated single organisms in 36 cases (59%) and polymicrobial growth in 25 cases (41%). The most frequently identified pathogens were Streptococcus anginosus (n=40, 66%) followed by Fusobacterium species (n=10, 16%) and Prevotella species (n=10, 16%). Most cases were treated with combination antibiotic therapy (n=68, 63%) and 14% (n=15) with a carbapenem. The median duration of intravenous antibiotic therapy was 51 days (IQR 42-80). One child died and 23% (n=25) suffered neurological sequelae (median follow-up 344 days). 48 cases (44%) occurred between 2014-2019. Conclusion: Intracranial complications of sinusitis continue to cause significant morbidity in children. The predominant causative pathogen was Streptococcus anginosus . Polymicrobial infections are common, confirming the need for prolonged broad-spectrum antibiotic treatment. Disclosures: Sharon Cushing, MD, MSc, FRCSC, Cochlear Corporation (Research Grant or Support)Cochlear Corporation (Speaker's Bureau)Interacoustics (Speaker's Bureau)Plural publishing (Other Financial or Material Support, Royalties: editor: manual of pediatric balance disorders)